Exploring physical performance and coaches` expectations to understand the international selection process in cerebral palsy football - Peña-González, I.; Maggiolo, J. F.; Henríquez, M.; Cervelló, E.; Moya-Ramón, M. (Sport Sciences for Health, 2025)
Purpose This study aimed to explore the influence of player`s physical performance and coaches` efficacy expectations in the talent identification and selection process in international football for people with cerebral palsy (CP).